2013
DOI: 10.1021/nl4033457
|View full text |Cite
|
Sign up to set email alerts
|

Local Heating with Lithographically Fabricated Plasmonic Titanium Nitride Nanoparticles

Abstract: Titanium nitride is considered a promising alternative plasmonic material and is known to exhibit localized surface plasmon resonances within the near-infrared biological transparency window. Here, local heating efficiencies of disk-shaped nanoparticles made of titanium nitride and gold are compared in the visible and near-infrared regions numerically and experimentally with samples fabricated using e-beam lithography. Results show that plasmonic titanium nitride nanodisks are efficient local heat sources and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
198
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(205 citation statements)
references
References 45 publications
(61 reference statements)
7
198
0
Order By: Relevance
“…As a result, no improvement in the Q over the metallic case is expected. Values of Q in the range of 2-6 have been calculated for n-InGaAs [29], with similar results observed for heavily doped wide-gap oxides and nitrides such as AZO [30,31], GZO [32], ITO [30,31], and TiN [26], with Q values on the order 10 [120]. However, recent work within n-type CdO demonstrates Q on the order of 40, similar to plasmonic metallic systems, while offering resonances in the mid-IR, thus providing a promising alternative plasmonic material [33].…”
Section: The Promise Of Phonon Polaritons: a Comparison With Plasmonicssupporting
confidence: 76%
See 1 more Smart Citation
“…As a result, no improvement in the Q over the metallic case is expected. Values of Q in the range of 2-6 have been calculated for n-InGaAs [29], with similar results observed for heavily doped wide-gap oxides and nitrides such as AZO [30,31], GZO [32], ITO [30,31], and TiN [26], with Q values on the order 10 [120]. However, recent work within n-type CdO demonstrates Q on the order of 40, similar to plasmonic metallic systems, while offering resonances in the mid-IR, thus providing a promising alternative plasmonic material [33].…”
Section: The Promise Of Phonon Polaritons: a Comparison With Plasmonicssupporting
confidence: 76%
“…The search for alternative materials for nanophotonic and metamaterial applications can be broken into two major research thrusts: 1) identifying novel, lowerloss, free-carrier-based plasmonic materials and 2) exploring the use of dielectric materials. In the case of the former, efforts have focused on metal alloys [26][27][28], highly doped semiconductors [29][30][31][32][33] and more recently, graphene [34][35][36][37][38][39][40]. While the spectral range for localized plasmonic modes has been successfully pushed into the infrared using such materials, the plasmonic origin of the modes implies that they are still limited by the relatively fast electron/plasma scattering (typically on the order of 10-100 fs) [41][42][43].…”
Section: Introduction To Surface Phonon Polaritonsmentioning
confidence: 99%
“…We have previously shown that TiN nanoparticles provide field enhancement comparable to that achievable with Au, with a broader peak spectrally positioned in the biological transparency window [17]. In a more recent study, we experimentally analyzed the absorption efficiencies of lithographically fabricated TiN and Au nanoparticles and showed that TiN nanoparticles can provide enhanced local heating in the biological transparency window when compared to identical Au samples [18].…”
mentioning
confidence: 97%
“…TiN is a chemically inert material widely used in CMOS and biomedical devices [5,[27][28][29][30]. Combined with the localized surface plasmon resonance (LSPR) peak located in the biological transparency window [17], bio-compatibility of the material makes it a promising alternative for plasmonic photothermal therapy [18]. Consequently, the plasmonic properties of TiN colloidal nanoparticles are clearly important for future studies on the feasibility of the material for therapeutic applications.…”
mentioning
confidence: 99%
“…This issue has been discussed in [80], which suggests a generalized form of the scattering efficiency, called the near-field intensity efficiency, as a more comprehensive FOM for large scatters in LSP applications. Additionally, a recent work [81] demonstrated the absorption efficiency of particles as the critical FOM for local heating applications. Recently, there is a significant interest in searching for alternative low-loss plasmonic materials [76,[82][83][84][85][86], and applying these materials in SP, LSP, transformation optics, and metamaterials.…”
Section: Nft Self-heating and Materials Choicementioning
confidence: 99%